Global polarization of [lambda] hyperons in Au+Au collisions at √sNN=200 GeV - Adam, Jaroslav; Deppner, Ingo Martin; Herrmann, Norbert (Physical review, 2018)
Global polarization of Λ hyperons has been measured to be of the order of a few tenths of a percentage in Au+Au collisions at √sNN = 200 GeV, with no significant difference between Λ and ¯¯¯Λ. These new results reveal the collision energy dependence of the global polarization together with the results previously observed at √sNN = 7.7-62.4 GeV and indicate noticeable vorticity of the medium created in noncentral heavy-ion collisions at the highest Relativistic Heavy Ion Collider collision energy. The signal is in rough quantitative agreement with the theoretical predictions from a hydrodynamic model and from a multi-phase transport model. The polarization is larger in more peripheral collisions, and depends weakly on the hyperon's transverse momentum and pseudorapidity ηH within ∣∣ηH|<1. An indication of the polarization dependence on the event-by-event charge asymmetry is observed at the 2σ level, suggesting a possible contribution to the polarization from the axial current induced by the initial magnetic field.
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol, "NN" ist dabei tiefgestellt
Im Titel ist "lambda" als griechischer Buchstabe dargestellt
Gesehen am 05.07.2019